Comparison of lateral parapatellar vs. infrapatellar approaches for intramedullary nailing for tibial shaft fractures - Yang, Lifeng; Nie, Guanghua (Frontiers in Surgery, 2025)
BackgroundThis study aimed to evaluate the clinical and functional outcomes of tibial shaft fractures treated with intramedullary nailing (IMN) using the lateral parapatellar entry (LPE) and infrapatellar (IP) surgical approaches.MethodsA total of 85 patients with tibial shaft fractures treated with IMN between January 2019 and December 2022 were retrospectively analyzed. A total of 40 and 45 patients underwent IMN using the LPE and IP surgical approaches, respectively. The operation time, intraoperative fluoroscopy times, blood loss, closed reduction rate, fracture healing time and complications were reviewed in this study. The American Orthopaedic Foot and Ankle Society (AOFAS) scale and Lysholm Knee Scoring Scale were used as functional measurements.ResultsThe study included 85 patients (40 in the LPE group and 45 in the IP group), with a minimum follow-up of 12 months. No significant differences were found in fracture healing time, closed reduction rate, infection, deformity healing rate, Lysholm scores, and AOFAS scores between the groups. The LPE group displayed an significantly shorter operation duration, less blood loss, fewer fluoroscopy times, and a lower average VAS score compared to the IP group (P < 0.05).ConclusionsThe LPE approach for IMN in tibial shaft fractures may offer advantages in terms of fewer fluoroscopy times, and lower complication rates, suggesting it could be a preferable surgical approach.